Enhancing the Efficacy of Tumor Vaccines Based on Immune Evasion Mechanisms - Chen, Jianyu; Zhang, Honghao; Zhou, Lijuan; Hu, Yuxing; Li, Meifang; He, Yanjie; Li, Yuhua (Frontiers in Oncology, 2021)
Tumor vaccines aim to expand tumor-specific T cells and reactivate existing tumor-specific T cells that are in a dormant or unresponsive state. As such, there is growing interest in improving the durable anti-tumor activity of tumor vaccines. Failure of vaccine-activated T cells to protect against tumors is thought to be the result of the immune escape mechanisms of tumor cells and the intricate immunosuppressive tumor microenvironment. In this review, we discuss how tumor cells and the tumor microenvironment influence the effects of tumor infiltrating lymphocytes and summarize how to improve the efficacy of tumor vaccines by improving the design of current tumor vaccines and combining tumor vaccines with other therapies, such as metabolic therapy, immune checkpoint blockade immunotherapy and epigenetic therapy.